Impact and reliability analysis of voltage sags in a multi-pulse transformer-fed variable frequency drive system - R. Govarthanan; K. Palanisamy; S. Paramasivam (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
In an industrial grid, variable frequency drives (VFDs) are the major appliances that contribute to harmonic pollution. To reduce the effects of this harmonic pollution and comply with the regulatory standards, multi-pulse transformers are used to cancel out the specific harmonics. The VFDs experience a different input current profile when fed through multi‑pulse transformers compared to direct grid connection. Despite the harmonic pollution reduction in the grid due to this implementation, the current stresses faced by the front-end devices will become higher. If the VFDs are designed only considering the impact of the direct grid consideration, the lifetime and reliability of the front-end devices will be a concern if operated with a multi-pulse feeder. This condition will be worse if there are presence of different types of sag events. This research details the effects of the reflected sags in the multi-pulse transformer’s secondary windings and the current stresses in the different front-end converter elements due to this. Also, a systematic methodology using the FIDES approach is used to estimate the reliability of the front-end converter. A 7.5 kW-rated VFD is fed with a 12-pulse transformer is used for this research.